If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+5(3/2)=7
We simplify the equation to the form, which is simple to understand
6x+5(3/2)=7
Reorder the terms in parentheses
6x+(+7.5)=7
Remove unnecessary parentheses
+6x+7.5=+7
We move all terms containing x to the left and all other terms to the right.
+6x=+7-7.5
We simplify left and right side of the equation.
+6x=-0.5
We divide both sides of the equation by 6 to get x.
x=-0.083333333333333
| -3(e-4)=6 | | 5(d-6)=20 | | ln(3t)=9 | | 1.2c-8=7 | | 8c-5=5c+7 | | 9-5b=19 | | 36x^2-72x-12y^2+48=0 | | 3x^2-8x+2=6 | | (7.12*10^15)/(3.5*10^9) | | 2x^2+x^2=75 | | 42x-5x=2x-1 | | 1+4X=XY | | 9h-23=67 | | 42x-3x=2x-1 | | 2x^2+5x-x^2=-4 | | 2x+10=-4x+30 | | u^2-16w+48=0 | | b/3x=8/15 | | (8u^4+7)+4u^4= | | 3(m-1)+2(m-2)=0 | | 16x-6x=4 | | 2-s+s=5-s+8 | | 16x^2-6x=4 | | x+(x+30)=31 | | -6x+2x=-12 | | (4a-4b)+2a= | | a^2+17a+72=0 | | 5x+9=87 | | 13-3x^2=-14 | | 5-c=2c+3 | | 0-y=-6 | | (7x^4-6y)+5x^4= |